Late fMRI Response Components Are Altered in Autism Spectrum Disorder - Murray, Scott O.; Kolodny, Tamar; Schallmo, Michael-Paul; Gerdts, Jennifer; Bernier, Raphael A. (Frontiers in Human Neuroscience, 2020)
Disrupted cortical neural inhibition has been hypothesized to be a primary contributor to the pathophysiology of autism spectrum disorder (ASD). A prediction of this hypothesis is that ASD will be associated with an increase in neural responses. We tested this prediction by comparing fMRI response magnitudes to simultaneous visual, auditory, and motor stimulation in ASD and neurotypical (NT) individuals. No increases in the initial transient response in any brain region were observed in ASD, suggesting that there is no increase in overall cortical neural excitability. Most notably, there were widespread fMRI magnitude increases in the ASD response following stimulation offset, approximately 6-8 seconds after the termination of sensory and motor stimulation. In some regions, the higher fMRI offset response in ASD could be attributed to a lack of an ‘undershoot’ – an often observed feature of fMRI responses believed to reflect inhibitory processing. Offset response magnitude was associated with reaction times in the NT group and may explain an overall reduced reaction time in the ASD group. Overall, our results suggest that increases in neural responsiveness are present in ASD but are confined to specific components of the neural response, are particularly strong following stimulation offset, and are linked to differences in reaction time.